SOME PROBLEMS SOLUTION OF THE THEORY OF VIBRATIONS WITH REGARD TO THE ROLLING FRICTION - Bondarenko, L. M.; Kolbun, V. V. (Science and Transport Progress, 2007)
The row of tasks of theory of vibrations is decided with the use of dependences for analytical determination of coefficient of friction of cachenie.